Perbedaan Peningkatan Kemampuan Berpikir Kritis dan Kreatif Matematis Siswa Melalui Penerapan Model PBL di SMP Nurul Huda Medan - Darmiati, Darmiati; Panjaitan, Dedy Juliandri; Destini, Rita; Zahari, Cut Latifah (Media Pendidikan Matematika, 2026)
This study aimed to analyze differences in the improvement of students’ mathematical critical and creative thinking abilities between Problem Based Learning (PBL) and direct instruction. The study used a quasi-experimental method with a pretest-posttest control group design. The population was all eighth-grade students of SMP Nurul Huda Medan, and the samples were class VIII-A as the experimental group (28 students) and class VIII-B as the control group (29 students), selected through random sampling. Data were collected using essay tests measuring mathematical critical and creative thinking on similarity material, supported by observation and documentation. The data were analyzed using normalized gain, Kolmogorov-Smirnov normality test, Levene homogeneity test, Mann-Whitney test, independent sample t-test, and Pearson correlation. The results showed that PBL produced higher improvement than direct instruction. The mean N-gain of critical thinking was 0.479 in the PBL group and 0.381 in the direct instruction group, with Mann-Whitney significance of 0.003. The mean N-gain of creative thinking was 0.533 in the PBL group and 0.435 in the direct instruction group, with t-test significance of 0.013. Critical and creative thinking also had a strong positive correlation (r = 0.727; p = 0.000). Therefore, PBL is effective for improving students’ mathematical critical and creative thinking abilities.